2017
DOI: 10.1787/7d5dcae6-en
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Spatial Thinking to Support Stem Learning

Abstract: HARNESSING SPATIAL THINKING TO SUPPORT STEM LEARNING Unclassified OECD EDUCATION WORKING PAPERS SERIES OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed herein are those of the author(s). Working Papers describe preliminary results or research in progress by the author(s) and are published to stimulate discussion on a broad range of issues on which the OECD works. Comments on Working Papers are wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 199 publications
(186 reference statements)
0
28
1
Order By: Relevance
“…Foodhoarding birds rely on spatial memory to retrieve their caches, which is crucial to their subsistence, and climate harshness has been found to positively drive the evolution of spatial memory skills in black-capped chickadee, another bird species 1 . Spatial skills are also important in modern technologically oriented societies 2,3 as individual differences in spatial skills are associated with positive developmental, educational and life outcomes. Spatial ability reliably predicts scholastic and professional success and career choices, particularly in Science, Technology, Engineering and Mathematics (STEM) and related fields, even after controlling for general cognitive ability [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foodhoarding birds rely on spatial memory to retrieve their caches, which is crucial to their subsistence, and climate harshness has been found to positively drive the evolution of spatial memory skills in black-capped chickadee, another bird species 1 . Spatial skills are also important in modern technologically oriented societies 2,3 as individual differences in spatial skills are associated with positive developmental, educational and life outcomes. Spatial ability reliably predicts scholastic and professional success and career choices, particularly in Science, Technology, Engineering and Mathematics (STEM) and related fields, even after controlling for general cognitive ability [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Spatial ability reliably predicts scholastic and professional success and career choices, particularly in Science, Technology, Engineering and Mathematics (STEM) and related fields, even after controlling for general cognitive ability [4][5][6] . In spite of the increasingly fundamental role that spatial ability has for individuals and contemporary societies 3 , numerous questions remain regarding the nature of spatial ability as well as its origins and structure 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is an ongoing debate about whether we build a detailed cognitive map or a much simpler cognitive graph of the possible physical choice points 30,31 inside our head. Furthermore, recent studies reported major correlations between the navigation and learning skills of humans 32,33 , while others went even further and investigated the possibility that navigation in cognitive spaces may lie at the core of any form of organized knowledge and thinking [34][35][36] . The word-morph network is a special mixed system over which navigation relies strongly on domain-general mechanisms since both spatial, manifested in the Hamming distance between words, and cognitive, i.e., the function and meaning of the words, dimensions contribute to the formation paths.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is an ongoing debate about if we build a detailed cognitive map or a much simpler cognitive graph of the possible physical choice points 20,21 inside our head. Furthermore, recent studies reported major correlations between navigation and learning skills of humans 22,23 while others go even further and investigate the possibility that navigation in cognitive spaces may lie in the core of any form of organized knowledge and thinking [24][25][26] . The word-morph network is a special mixed system over which navigation relies strongly on domain-general mechanisms since both spatial, manifested in the Hamming distance between words, and cognitive dimensions, i.e.…”
Section: Introductionmentioning
confidence: 99%